Public Trust Reloaded: The Impact of Data Transparency and Digital Participation on Government Legitimacy in the Era of Open Government - Tunggul Prasodjo (Manunggal Halim Jaya, 2026)
This study aims to explore how data transparency and digital participation influence public trust and government legitimacy in the contemporary era of open government. Through a qualitative literature-based approach, the research synthesizes recent theoretical and empirical findings published between 2015 and 2025, encompassing studies on transparency, e-participation, and institutional trust across diverse political and cultural contexts. Data were collected from reputable databases such as Scopus, ScienceDirect, and SpringerLink, and analyzed using qualitative content analysis to identify conceptual patterns and thematic relationships among the key constructs. The results indicate that data transparency enhances perceptions of government competence and integrity, while digital participation fosters inclusiveness and responsiveness, together generating a multidimensional form of legitimacy. However, these effects are contingent on the quality, accessibility, and sincerity of transparency practices as well as on the meaningfulness of participatory mechanisms. The study also finds that trust functions both as an outcome and as a mediating variable, moderating how citizens interpret openness and accountability. Theoretically, this research contributes to the integration of Legitimacy Theory and Trust Theory by demonstrating that legitimacy in the digital era is co-produced through communicative interaction and ethical transparency. Managerially, the findings imply that open government must evolve toward sustainable governance by institutionalizing transparency and digital participation as continuous, ethical, and inclusive processes. The study concludes that enduring legitimacy requires adaptive institutions capable of aligning openness with technological transformation, citizen expectations, and responsible data stewardship.